Outcomes of Total Hip Arthroplasty in Patients With Acetabular Protrusio. (July 2020) - Greig, Danielle; Hsiue, Peter P.; Chen, Clark J.; Trikha, Rishi; Khoshbin, Amir; Stavrakis, Alexandra I.
Abstract : Background: Acetabular protrusio (AP) is associated with distorted anatomic landmarks and insufficient bone stock that increases complexity of total hip arthroplasty (THA). This study used a large national database to compare outcomes after THA in patients with and without AP. Methods: The Nationwide Readmissions Database was used to identify patients with and without AP who underwent THA from 2010 to 2014. Primary outcomes analyzed included complications during index hospitalization and within 90 days of THA. Results: Propensity score matching generated 4, 395 patients without AP and 4, 603 patients with AP. Patients with AP were older (68.1 versus 65.2 years, P < 0.0001), more predominantly women (82.1% versus 55.9%), and had more medical comorbidities as measured by the Elixhauser Comorbidity Index (2.29 versus 1.89, P < 0.0001). Patients with AP had an increased risk of requiring bone graft (odds ratio [OR] = 47.97, 95% confidence interval [CI]: 14.27 to 161.22), receiving a blood transfusion (OR = 1.90, 95% CI: 1.57 to 2.29), and suffering a periprosthetic fracture (OR = 2.56, 95% CI: 1.10 to 5.97) within 90 days of THA. Length and cost of index hospitalization were greater for patients with AP (5.0 versus 4.3 days, P = 0.002; $19, 211.88 versus $27, 736.30, P < 0.0001). Conclusion: Given the current emphasis on hospital cost optimization, it is important to ensure that patients with AP are managed appropriately. Attention should be placed on comprehensive preoperative planning and postoperative monitoring in this population.